મદયયુગના ભારતનો ઇતિહાસ, ધોરણ સાતમું - (:unkn) unknown (Maharashtra State Bureau of Textbook Production & Curriculum Research, 2010)
The book is on The History of Medieval India written in Gujarati language.
Keywords: Gujarati; મદયયુગના ભારતનો ઇતિહાસ; ધોરણ સાતમું; History; Gujarati; Gujarati